BUKU DIGITAL PRAKTIK AKUNTANSI JASA (BUDIAJA) AS A LEARNING SUPPORT IN THE INTRODUCTION TO ACCOUNTING COURSE - Purwanto Nuri; Utomo Langgeng Prayitno; Mutiarni Rita (STIE PGRI Dewantara Jombang, 2023)
As one of the leading universities in Jombang, STIE PGRI Dewantara Jombang strives to provide the best possible service to all students with various abilities, including students who are slow learners. A learning aid technology was created that makes it easier for students to carry out lectures, one of which is the Introduction to Accounting course. This activity aims to create learning aids technology to make it easier for students to absorb the lesson with the BUDIAJA application. This activity lasted approximately five months, from the preparation stage to the final evaluation of the activity. This activity involved the writing team, a professional software developer, 20 volunteer students, and educational technology consultants. From the results of the activity, it is known that the response given by students after using BUDIAJA was very good and increased understanding. The follow-up plan for this activity is to develop the program so that it can be applied to other courses.